4.2: Invited Paper: Development of High Mobility Zinc Oxynitride Thin Film Transistors. Issue 1 (1st July 2013) - Ye, Yan; Lim, Rodney; You, Harvey; Scheer, Evelyn; Gaur, Anshu; Hsu, Hao‐chien; Liu, Jian; Yim, Dong Kil; Hosokawa, Aki; White, John M.
Abstract Possible mechanisms to achieve high mobility in zinc oxynitride (ZnON) have been investigated by comparison with other thin film semiconductors. Integrated processes to fabricate ZnON TFTs have been developed. Issues and challenges encountered at current stage will be discussed.